An analytical solution for aerosol penetration in the slip flow regime. (January 2022) - Jia, Feng; Huang, Wei; Pui, David Y.H.; Tsai, Chuen-Jinn
Abstract: The classical theory for the diffusional loss of aerosol particles in a fully developed laminar flow through a circular tube derived by Gormley and Kennedy (1949) did not consider the slip-flow condition. However, the non-slip condition for the gas velocity boundary condition may not be appropriate for the gas flow in microgeometries such as microchannels and microtubes. This paper extends the work of Gormley and Kennedy (GK) to include the effect of slip-flow, which often occurs in the gas flow at low pressure or with a small characteristic length scale. In the present solution, the separation of variables was applied to solve the convection-diffusion equation, then confluent hypergeometric function was used to solve for the number concentration as a function of radial distance analytically. Eigenvalues were evaluated for Knudsen numbers ranging from 0.001 to 0.1. Finally, a simple power series correlation was developed to describe aerosol penetration in the slip flow regime as a function of the dimensionless deposition factor and Knudsen number ( Kn ). In the slip flow regime, the penetration decreases with increasing Kn . The correlation is reduced to GK's solution when Kn = 0. The present solution of aerosol penetration calculated at Kn = 0 shows good agreement with GK's solution and validates the applicable range of the approximate solution by Alonso et al. (2016) . Graphical abstract: Image 1 Highlights: The work of Gormley and Kennedy was extended to include the effect of slip-flow. The number concentration as a function of radial distance was solved using confluent hypergeometric function. The penetration decreases with increasing Knudsen number in the slip flow regime.